Changing Behaviour of Middle-Class Households towards Risk & Return Perception for Investment - Chaman Kumar; Dr. Vijay Kumar (International Journal of Engineering and Management Research, 2021)
There has been an enormous amount of information collected over the past decade about financial markets and financial institutions. Middle class households’ investors are far less well understood. Investing motivations and risk perceptions of investors, as well as investor risk perceptions and attitudes, are examined here. It is also examined how income and investing pattern relate to risk and returns. Portfolio managers and investors are faced with the dilemma of balancing risk and return. Investors generally aren't motivated to take risks for their own sake, according to the convention in finance and economics. Then it would seem feasible to expect that actual yields on individual investment may deviate according to their risks. There is consensus that there is a positive relationship between risk and expected return, even if the conclusions are not totally consistent concerning the shape of the risk-return function. The aim of this paper is to demonstrate that risk-return preferences and motives of investors can be addressed by analyzing the investments. This empirical study has been designed to analyse the middle-class households risk preference over the last decade in the Kumaun division using structure schedule for 250 households. Researcher used linear regression, anova, coefficient, chi-square test and factor analysis model to explore the problem. It is found that people attitude towards have been changed in the last decade towards risk and return trade off and they are reshaping their motives of investment with the change in time.